Retracing the contours of the early angiosperm environmental niche. (12th August 2019) - Pouteau, Robin; Trueba, Santiago; Isnard, Sandrine
Abstract: Background and Aims: Our aim was to understand the environmental conditions of the emergence and radiation of early angiosperms. Such a question has long remained controversial because various approaches applied in the past have drawn conflicting images of early angiosperm ecology. Methods: We provided a new perspective on the question by using support vector machines to model the environmental niche of 51 species belonging to ten genera of extant lineages that diverged early during angiosperm evolution (basal angiosperms). Then, we analysed the resulting pattern of niche overlap and determined whether this pattern deviates from what would be expected on the basis of a null model or whether it might mirror a legacy of a common primitive niche based on a phylogenetic reconstruction. Key Results: The niche of three-quarters of the species and all genera converged towards tropical montane cloud forests (TMCFs). The latitudinal pattern of basal angiosperm richness indeed culminated in the tropics, and the elevational pattern revealed a humpback curve peaking between 2000 m and 3500 m when accounting for the effect of area. At first glance, this diversity pattern does not significantly differ from null predictions. However, we revealed a tendency for the basal-most taxa to occur in TMCFs so that phylogenetic reconstructions indicated that the niche of the common ancestor of the sampled basal angiosperms had a probability of 0.85–0.93 to overlap with TMCFs. Conclusions: Our new approach indicates that the environmental convergence of extant basal angiosperms towards TMCFs would reflect a legacy of an ancestral niche from which the least basal taxa would have diverged following a random pattern under geometric constraints.